ANALISIS PENILAIAN KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) (Studi Pada PT. Bank Muamalat Indonesia Tbk) - Sitti Nurnaluri; La Ode Anto; Nining Elfia (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2021)
This research aims to determine the financial performance of PT Bank Muamalat Indonesia Tbk using the Economic Value Added (EVA) method. The data analysis technique used in this research is descriptive qualitative analysis. Research data collection using documentation techniques. The results showed the calculation of Economic Value Added (EVA) at PT. Bank Muamalat Indonesia Tbk from 2017-2019 produced a positive EVA value or EVA value at PT. Bank Muamalat Indonesia is greater than zero (EVA> 0). This shows that there is economic added value for the company. Although the net profit of PT. Bank Muamalat Indonesia in 2017-2019 has decreased from previous years, but in this position PT Bank Muamalat Indonesia Tbk can still create economic added value for the company. This positive result was due to the large NOPAT value which was able to reduce the cost of capital, so that the company management was able to create economic added value for the company and its shareholders. so that the company's financial performance can be said to be in a good position.